Organizational Learning and Employee Performance: The Role of Competence as a Mediating Variable - Sintia; Santati, Parama; Farla, Wita; Hadjri, Muhammad Ichsan (Global Writing Academica Researching and Publishing, 2023)
Learning organizations play a pivotal role in enhancing employee performance, as organizations fostering a robust learning culture can offer the necessary support and development to enhance employee skills, knowledge, and effectiveness. Enhancing employee competency holds utmost importance in boosting performance, as employees equipped with skills, knowledge, and attitudes aligned with job requirements can operate more proficiently and productively. This study aims to examine the impact of learning organizations on performance, with competency serving as an intermediary variable. Conducted at PT Bumitama Gunajaya Agro, this research employs Structural Equation Modeling via LISREL 8.8 software for data analysis. The sample comprises 150 employees from PT Bumitama Gunajaya Agro. Model suitability is assessed using the Chi-Square test, RMSEA, CFI, and GFI. Findings indicate that learning organizations significantly enhance employee performance. Additionally, competency serves as a positive mediator in the relationship between learning organization and performance. These results underscore the significance of implementing learning organization principles, which involve employees in learning initiatives, to enhance competency and subsequently boost employee performance.